Developing a user-informed intervention study of a virtual reality therapy for social anxiety in autistic adolescents. Issue 1 (2nd January 2022) - Adams, Lucy; Simonoff, Emily; Tierney, Kevin; Hollocks, Matthew J.; Brewster, Aylana; Watson, Jennifer; Valmaggia, Lucia
Abstract: Social anxiety is prevalent in autistic adolescents. Using virtual reality to deliver exposure tasks in cognitive behavioural therapy (VRCBT) – the treatment-of-choice – may improve its accessibility in autism spectrum disorder (ASD). In preparation for testing this, service-providers (i.e. clinicians experienced with this patient group; n  = 17), service-users (i.e. autistic adolescents diagnosed with social anxiety; n  = 5), and their parents/guardians ( n  = 5), from local National Health Service (NHS) clinics specialized in working with ASD, were consulted. The aim was to develop user-informed case series, treatment, and VR design protocols for testing the intervention for the first time. Consultees indicated that the VRCBT exposure tasks ought to be self-paced, as individualizable as possible, viewable to the therapist, and provide a step towards real-life exposure. Consultees identified exposure tasks for simulating in VR: approaching and conversing with others, experiencing perceived injustice, the feeling of being the centre of attention, and situations involving novelty and/or lower predictability. Further implications for developing and testing VRCBT and conducting patient and public involvement (PPI) in autistic adolescents with social anxiety are discussed.